The Mirror’s Deception a Feminist Analysis of the Song ‘Who Says’ by Selena Gomez - Asti A Sirait; Jamaluddin Nasution; Alya Wardhani; Citra N E Hasugian; Dwi A J Sitanggang (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study examines feminist values in the lyrics of the song “Who Says” performed by Selena Gomez. This song was chosen because it contains messages about self-confidence, self-acceptance, and rejection of the beauty standards often imposed on women by society. The objectives of this study are to identify the feminist values present in the song’s lyrics, analyze how the song conveys messages about self-confidence and self-acceptance, and determine how the lyrics challenge societal standards regarding women. This study employs a qualitative descriptive method with a feminist approach. The research data consists of the lyrics of “Who Says,” which were analyzed using content analysis to uncover the feminist meanings and messages embedded within them. The results indicate that this song highlights the importance of women valuing themselves without conforming to society’s beauty standards. Furthermore, the song emphasizes that every individual has inherent value and uniqueness, thereby eliminating the need to feel inferior because of others’ judgments. Through these messages, the song “Who Says” can be interpreted as a form of resistance against the social pressures and stereotypes women frequently face. This study is expected to provide insight into how music can serve as a medium for conveying feminist messages and for building women’s self-confidence.